A morphology and histological study of placenta in normal and diabetic pregnancies - Tandon, Ashutosh; Singh, Durgesh; Mishra, Parmatma Prasad; Mishra, Anshu (International Journal of Research in Medical Sciences, 2018)
Background: The placenta is a vital organ for developing foetus, and it is also the most accessible organ of human body, pregnancy in a diabetogenic state by virtue of various physiological changes which cause insulin resistance. In normal pregnancy, glucose tolerance decreases by third trimester, though plasma levels of insulin increase. Aim was to study comparison of placenta of normal pregnancy with placenta of diabetic pregnancy and it the possible outcome of pregnancy. Methods: The present study was case-control and conducted on cases of 50 Specimens of placenta with intact umbilical cord were collected from the Department of Obstetrics and Gynecology. Results: Variation in the shape and weight of the placenta were observed. The mean placenta weight in control group was found to be 452.80 grams with standard deviation 140.93 grams while in the case group; it was 406.00 grams with standard deviation of 210.31 grams. The random blood sugar of mother in control group was significantly higher than cases (t=2.91, p<0.01). Conclusions: The present study shown that there was a tendency of increase in placental weight and weight of new born in complicated pregnancies as compared to the normal pregnancies. This indicated the earlier diagnosis and strict to treatment plan in diabetic pregnancies.